2009 - 2010 The best expression of architecture business & cultrue (China : Hua zhong ke ji ta xue chu ban she, 2010)
Effect diagram is a mirror that reflects the city's construction, growth, and even confused. This is a can not explain the huge portrait, and numerous renderings on the number of grams of coated paper through a different, but only slightly to left superficial glimpse of the city, the sky's color or blue or dull, or quiet street or noisy, buildings Lan lines stands in the center spot, layer upon layer, along a strip repeatedly pondering veins eventually characterize every seat under the city's silhouette.
Keywords: Buildings -- Performance; Buildings